2021
DOI: 10.1111/cgf.14359
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Optimization for Shape Matching

Abstract: We propose a novel discrete solver for optimizing functional map‐based energies, including descriptor preservation and promoting structural properties such as area‐preservation, bijectivity and Laplacian commutativity among others. Unlike the commonly‐used continuous optimization methods, our approach enforces the functional map to be associated with a pointwise correspondence as a hard constraint, which provides a stronger link between optimized properties of functional and point‐to‐point maps. Under this har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 65 publications
(95 reference statements)
0
54
0
Order By: Relevance
“…In [MRR*19] it is observed that a particular case of such problems can be efficiently solved by considering the two maps as being independent variables. This observation was recently extended to a wide range of energies in [RMWO21]. Following this line of work we will move all of the difficult optimization on the side of the vertex-to-vertex map and use Equation (10) to restore the relationship between the maps.…”
Section: Energy Minimization Via Nearest Neighbor Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…In [MRR*19] it is observed that a particular case of such problems can be efficiently solved by considering the two maps as being independent variables. This observation was recently extended to a wide range of energies in [RMWO21]. Following this line of work we will move all of the difficult optimization on the side of the vertex-to-vertex map and use Equation (10) to restore the relationship between the maps.…”
Section: Energy Minimization Via Nearest Neighbor Searchmentioning
confidence: 99%
“…Specifically, the first term promotes FscriptMN$F_{{\mathcal {MN}}}$ being a proper functional map (i.e. the pullback of a vertex‐to‐vertex map), as recently defined in [RMWO21], and the second promotes the invertibility of FscriptMN$F_{{\mathcal {MN}}}$ [ERGB16].…”
Section: Functional Map Energymentioning
confidence: 99%
See 3 more Smart Citations